Fabrication of attapulgite-based dual responsive composite hydrogel and its efficient adsorption for methyl violet. Issue 10 (29th April 2022) - Liu, Yi-xin; Zhong, Hui; Li, Xiao-rong; Bao, Zhuan-li; Cheng, Zhi-peng; Zhang, Yu-jie; Li, Chun-xiang
ABSTRACT: In this work, attapulgite (ATP)-based dual sensitive poly (N-isopropylacrylamide-co-acrylic acid) composite hydrogel, P(NIPAM-co-AA)/ATP, was prepared by free radical polymerization. The prepared composite hydrogel was characterized via methods of scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), zeta potential analysis and Brunauer, Emmett, and Teller (BET) etc. The composite hydrogel showed pH and temperature sensitive behaviour, with lower critical solution temperature (LCST) of 35°C and highest swelling occurred at pH 8.0. The adsorption of methyl violet (MV) can be controlled by the hydrogel responsiveness, and 95.78% of MV can be removed at pH 8.0 and 35°C. The addition of a small amount of ATP (3 Wt%) can improve the swelling ratio and adsorption capacity. Kinetic analysis demonstrated that the experimental data were best fitted to the pseudo-second order model. Isotherm analysis showed that the equilibrium data followed Langmuir model with the adsorption capacity of 168.35 mg g −1 . In addition, the composite hydrogel has high adsorption selectivity for cationic dyes, and MV-loaded hydrogel is easy to regenerate, which can be used for successive adsorption cycles. These results demonstrate that the composite hydrogel has potential application in dye wastewater treatment. GRAPHICAL ABSTRACT: UF0001